Feasibility study on the mhGAP‐IG as a tool to enhance parental awareness of symptoms of mental disorders in lower primary (6‐10 year old) school‐going children: Towards inclusive child mental health services in a Kenyan setting. Issue 3 (14th April 2020) - Mutiso, Victoria; Musyimi, Christine; Tele, Albert; Gitonga, Isaiah; Ndetei, David
Abstract: Aims: (1) To determine the feasibility of involving parents as key partners in school mental health activities; (2) to determine whether educating parents on mental health treatment Gap Intervention Guideline (mhGAP‐IG) section on children leads to enhanced parent perception of mental health symptoms in their children; and (3) to determine context appropriate social demographic predictors of the parental awareness following the psychoeducation using the mhGAP‐IG children version. Methods: Consenting parents completed the Child Behaviour Checklist (CBCL) and the Brief Problem Monitor for Parents (BPM‐P) about their children at baseline and at 6 months post‐baseline respectively. Immediately after post‐baseline, they received psychoeducation on the importance of mental well‐being in children and how to recognize symptoms of mental disorders, using the mhGAP‐IG section on children. This psychoeducation was the intervention between baseline and 6 months post‐baseline. We analysed means of mental disorder symptoms and prevalence of the various mental syndromes/problems on the CBCL/BPM‐P scores to determine the statistical significance of the changes between baseline and 6 months. Results: Overall, there was significant increase ( P  < 0.05) in the symptoms mean scores and prevalence of syndromes/problems between baseline and 6 months post‐psychoeducation. However, there were some differences between urban and rural settings and in some parents and children socio‐demographics and gender that should be considered in individual cases. Conclusion: It is feasible to include parents in school mental health programmes as key stakeholders. The mhGAP‐IG section on children is a good tool for psychoeducation. However, there are predictors of outcomes that need further research.